Educational Policy: Understanding Tri Pusat Pendidikan (Education Centers) as Efforts to Reach Educational Objectives - Musbaing Musbaing (International Journal of Asian Education, 2020)
This paper seeks to offer an interpretation of the significance of the core of education in an attempt to achieve public policy goals. Some publications addressing approaches, techniques, and models of learning as a means of understanding the ideal education, but there are still deficiencies attributable to educators or adults who do not see the environment as a place of training. The paper aims to provide parents, teachers, and the community with knowledge so that education is a joint obligation so that cooperation in the education system is complete. "Tri Pusat Pendidikan" are three critical elements that play an essential role in learning and become the center of educational activities, namely family education (informal education), school training (formal education), and social education (non-formal culture). The "Tri Pusat Pendidikan" idea means that learning can be done anywhere and at any time, being a mutual obligation. This principle says the society and family have a balanced responsibility for the success of education offenders, and that it is not just schools that are made and regulated as organizations that have a great (full) responsibility for the success of individuals in their educational cycle.